2002
DOI: 10.1042/cs1030325
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia suppresses the secretion of ghrelin, a novel growth-hormone-releasing peptide: responses to the intravenous and oral administration of glucose

Abstract: Ghrelin is a novel growth hormone (GH)-releasing peptide, isolated from the stomach, which may also cause a positive energy balance by stimulating food intake and reducing fat utilization. However, whether glucose influences the release of ghrelin remains unknown. Accordingly, we examined circulating levels of ghrelin and GH in response to the intravenous or oral administration of 50 g of glucose in eight healthy humans. After the administration of intravenous glucose (50 g), the plasma ghrelin level decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
86
4
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(98 citation statements)
references
References 11 publications
5
86
4
3
Order By: Relevance
“…This is in agreement with a recent study with obese children. 23 However, there is ongoing debate whether glucose itself 13,24 or the accompanying rise in insulin levels decrease ghrelin as suggested by other authors. 12 A rise in ghrelin levels after weight loss has been demonstrated earlier in adults 8 and more recently in children, who were younger than in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a recent study with obese children. 23 However, there is ongoing debate whether glucose itself 13,24 or the accompanying rise in insulin levels decrease ghrelin as suggested by other authors. 12 A rise in ghrelin levels after weight loss has been demonstrated earlier in adults 8 and more recently in children, who were younger than in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown ghrelin to decrease in response to oral (Caixas et al, 2002;Nakagawa et al, 2002;Shiiya et al, 2002) or i.v. glucose (Nakagawa et al, 2002;Shiiya et al, 2002;Briatore et al, 2003), but others do not (Schaller et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown ghrelin to decrease in response to oral (Caixas et al, 2002;Nakagawa et al, 2002;Shiiya et al, 2002) or i.v. glucose (Nakagawa et al, 2002;Shiiya et al, 2002;Briatore et al, 2003), but others do not (Schaller et al, 2003). An inhibitory role of insulin on ghrelin has also been shown in some (Mohlig et al, 2002;Saad et al, 2002;Flanagan et al, 2003) but not all (Caixas et al, 2002;Schaller et al, 2003) studies.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental settings, glucose administration or food intake have been shown to decrease plasma ghrelin concentrations (7)(8)(9). Studies of the effects of ghrelin on insulin secretion have shown both stimulatory (10 -12) and inhibitory effects (13,14).…”
mentioning
confidence: 99%